Studying in Global Trend of Magazine Style - หอมแย้ม, ณพงศ (วารสารสถาบันวัฒนธรรมและศิลปะ, 2018)
This research aimed to study formats of elements of international magazine designs for instructional purposes in a course of designs of magazines and printing media. The result is presented in descriptive analysis. Observation and survey were employed in the data collection process. The data was collected from one hundred international fashion magazines. The study was divided into seven parts according to the different presentations of different types of magazines: covers, contents, contributors, imprints, editorials, interviews, articles, fashions, reviews and promotions. Purposive sampling was employed for samples from each type of magazines. All together there were 700 sample pages for analysis in this study. The study framework divided the survey into two major parts. The first one was verbal language such as typeface, characters, and alignment. The other was non-verbal language, including margins and grids. The result showed that in verbal language, Neo Grotesque and Transitional fonts were in trend. Normal, bold and light fonts were utilized. The flush left, centered and flush right alignments were common. In non-verbal language, equal and tiny margins were common. The study also found new patterns of margins which were the width of the margins. The bottom side was double of the rest; the top side was double and triple of the other sides; and the bottom side was normal while the rest was very narrow. The hierarchy, column and manuscript grids were common. According to the results, Global trend about the verbal language designs have stayed unchanged in typeface, characters and alignments. It was assumed that the reason the verbal language stayed unchanged was because the verbal language was the direct communication and no matter what types of magazines they were, or whoever target audience was, the letters had to be clear and easy to read. On the other hand for the non-verbal language : margins and grids, which were the implicit characters and meaning of the magazines, the designs tend to demonstrate the attempt to deviate from the traditional designs. There were adjustments of margins and grids in order to be different.